Fluorescence Characteristics of Hydrophobic Partial Agonist Probes of the Cholecystokinin Receptor. Issue 2 (22nd June 2006) - Harikumar, Kaleeckal G.; Pinon, Delia I.; Miller, Laurence J.
Abstract : Fluorescence spectroscopic studies are powerful tools for the evaluation of receptor structure and the dynamic changes associated with receptor activation. Here, we have developed two chemically distinct fluorescent probes of the cholecystokinin (CCK) receptor by attaching acrylodan or a nitrobenzoxadiazole moiety to the amino terminus of a partial agonist CCK analogue. These two probes were able to bind to the CCK receptor specifically and with high affinity, and were able to elicit only submaximal intracellular calcium responses typical of partial agonists. The fluorescence characteristics of these probes were compared with those previously reported for structurally-related full agonist and antagonist probes. Like the previous probes, the partial agonist probes exhibited longer fluorescence lifetimes and increased anisotropy when bound to the receptor than when free in solution. The receptor-bound probes were not easily quenched by potassium iodide, suggesting that the fluorophores were protected from the extracellular aqueous milieu. The fluorescence characteristics of the partial agonist probes were quite similar to those of the analogous full agonist probes and quite distinct from the analogous antagonist probes. These data suggest that the partially activated conformational state of this receptor is more closely related to its fully active state than to its inactive state.